Forecasting the number of food and beverage industries using trend-adjusted exponential smoothing in Banyuwangi after pandemic covid-19 - Darmawan, Randhi Nanang (Desimal: Jurnal Matematika, 2022)
The development of the tourism industry in Banyuwangi before the COVID-19 pandemic was quite rapid, including the food and beverage industries, but when the COVID-19 pandemic hit, it impacted the number of tourists in Banyuwangi decreasingly, and this had a significant impact on various economic sectors. However, interesting data showed that the number of food and beverage industries can be said to be stable during COVID-19, the trend indicated that there will be an increase in the number of the food and beverage industries after the pandemic subsides. In line with the Banyuwangi Rebound program, it is likely that the quantity of food and beverage industries will increase. Then, based on this phenomenon, the aim of this research was to forecast the number of food and beverage industries in Banyuwangi using the trend-adjusted exponential smoothing method. The accuracy and feasibility of forecasting results were measured based on the Mean Absolute Percentage Error (MAPE) and Tracking Signal (TS) values. The obtained forecasting model will be used to forecast the growth of the food and beverage industries in 2022, 2023, 2024, and 2025. The results of this research obtained that a forecasting model , with the results of forecasting the number of the food and beverage industries in Banyuwangi were 547 in 2022, 561 in 2023, 576 in 2024, and 589 in 2025. The average MAPE value for each forecasting result was 37.87% and the average TS value was 0.225, so it was included in the category of feasible to be used.